2SPD-002 Economic aspects of the use of fluids in sepsis. (2nd March 2018) - Peric, A; Kovačević, S Vezmar; Surbatovic, M
Abstract : Background: Fluid resuscitation is a central component of sepsis management, but which fluid should be used has remained controversally. The updated Survivng Sepsis Guidelines, published in 2016, recommends crystalloids as the initial choice for fluid resuscitation in sepsis with albumin as an adjuvant when patients require substantial ammounts of crystalloides. Purpose: The aim was to compare the costs of using crystalloids alone vs. crystalloids and albumin, as they are commonly used in the treatment of sepsis. Material and methods: The study was conducted from September 2016 to May 2017 in the Intensive Care Unit (ICU) of a tertiary university hospital. A group of 24 adult critically ill patients with sepsis who received crystalloids with 20% albumin (n=24), were included in the study. The control group consisted of age-, sex- and diagnosis-matched patients who were administered crystalloids alone (n=24). The cost of treatment, in the ICU, was calculated for both groups. Treatment outcomes were expressed in life-years gained (LYG) and quality-adjusted life-years (QALYs). LYG were adjusted for patients with sepsis (LYG/0.51). QALYs were obtained by multiplying adjusted LYGs with the utility value for sepsis 0.69. Student t-test was used for statistical analysis between groups. All costs are reported as median 95% confidence interval (CI). Results: There were no statistical differences regarding LYG and QALYs between the two groups. Costs were higher in the group with added 20% albumin in comparison to patients treated with crystalloids for €170 (95% CI: €125 to 214). Conclusion: The results showed that the use of 20% albumin, in critically ill patients with sepsis was associated with higher costs, with no differences in survival. Our results indicate that crystalloids alone should be the fluid of choice in patients with sepsis. Reference: Rhodes A, Evans L, Alhazzai W, et al. Surviving sepsis campaign: International guidelines for management of sepsis and septic shock: 2016. Crit Care Med2017;45(3):?1–67. No conflict of interest